P‐Aminophosphaalkenes with C‐Isopropyldimethylsilyl Groups. Issue 10 (7th May 2019) - Bîrzoi, Roxana M.; Jones, Peter G.; Bartsch, Rainer; du Mont, Wolf‐W.
Abstract : Amination of the C ‐isopropyldimethylsilyl P ‐chlorophosphaalkene ( i PrMe2 Si)2 C=PCl (1 ) leads to the P ‐aminophosphaalkenes ( i PrMe2 Si)2 C=PN( R ) R ′ ( R, R ′ = Me (2 ), R = H, R ′ = n Pr (3 ), R = H, R ′ = i Pr (4 ), R = H, R ′ = t Bu (5 ), R = H, R ′ = 1‐Ada (6 ), R = H, R ′ = CPh3 (7 ), R = H, R ′ = Ph (8 ), R = H, R R′ = 2, 6‐ i Pr2 Ph (= DIP) (10 ), R = H, R ′ = 2, 4, 6‐Me3 Ph (= Mes) (11 ), R = H, R ′ = 2, 4, 6‐ t Bu3 Ph (= Mes*)] (12 ), R = H, R ′ = SiMe3 (13 ), and R, R ′ = SiMe2 Ph (14 ). 31 P‐NMR spectra confirm that phosphaalkenes2 –7 and10 –14 are monomeric in solution; the structures of7, 10, and12 were determined by X‐ray crystallography. Freshly prepared ( i PrMe2 Si)2 C=PN(H)Ph (8 ) is a monomer that dimerizes with (N→C) proton migration within several hours to the stable diazadiphosphetidine [( i PrMe2 Si)2 CHPNPh]2 (9 ). NMR‐scale reactions of deprotonated5 and13 with t Bu i PrPCl provide by P–P bond formation the P ‐phosphanyl iminophosphoranes [( i PrMe2 Si)2 C=]( R N=)PP t Bu( i Pr) [ R = t Bu (15 ), R = Me3 Si (17 )]. Deprotonated5 and Me3 GeCl deliver by N–Ge bond formation the aminophosphaalkene ( i PrMe2 Si)2 C=PN( t Bu)GeMe3 (20 ), which with elemental selenium5 undergoes (N→C) proton migration to form the alkyl(imino)(seleno)phosphorane [( i PrMe2 Si)2 CH]( t BuN=)P=Se (21 ), which is a selenium‐bridged cyclic dimer in the solid state. Abstract :